Jejak Intelektual Al-Khawarizmi: Dari Khwarizm ke Pusat Ilmu Baghdad - Hermawan, Rudi; Hamdani, Arfan; Mulyanto, Mulyanto (Lembaga Yasin AlSys, 2025)
Abu Abdullah Muhammad Ibn Musa al-Khawarizmi stands as one of the most influential scholars in the history of Islamic and global civilization, recognized as a pioneer of algebra and a key figure in introducing the Hindu–Arabic numeral system and the concept of the algorithm—foundational to modern information technology. This study provides a descriptive analysis of al-Khawarizmi’s intellectual journey, from his early social and educational background in Khwarizm to his contributions at the Bayt al-Hikmah in Baghdad during the Abbasid Caliphate. At this institution, he not only translated scientific works from various civilizations but also developed original theories in mathematics, astronomy, and geography that had practical societal applications. The findings reveal that al-Khawarizmi exemplified the integration of scientific knowledge, Islamic spiritual values, and a strong scholarly ethic. His systematic, rational, and functional works laid critical foundations for the advancement of science in the West and symbolized the intellectual brilliance of classical Islamic civilization. These insights affirm the strategic role of the Islamic scholarly tradition in shaping the trajectory of global scientific development grounded in universal and humanistic values.